The Relationship between Staff's Cognitive Empowerment and Human Sources' Production in administrative & Financial deputy Abstract in Hashemenejad Hospital Of Tehran: 2012-2013 - AA Nasiripour; HR Pasha; KHA Mohammadzadeh (Tehran University of Medical Sciences, 2014)
Backgrounds: Explanation of Cognitive empowerment & Human Sources Productivity is theoretically & practically important . This research is aimed to examine the relationship between psychological empowerment of staff with human resources' productivity. Materials & Methods: This study is applied by purpose and survey by method and correlation was used to investigate the mentioned relationship . The statistical population consist of administrative and financial stuff of Hashemi Nejad hospital. The data were collected by questionnaire and interviewing and observing. Two types of questionnaire had been distributed among statistical samples for testing survey's hypotheses witch their questions were based on Likert scale of seven. First questionnaire's reliability was 0.95 and second one was 0.93. Due to achieve survey's objectives, both analytical and descriptive statistic had been used. Results: using Pearson correlation coefficient, the survey's testing hypothesis showed a significant correlation between component of cognitive empowerment and four variables of human recourses productivity (organizational commitment, organizational participation, job creativity and job satisfaction). The relationship between the empowerment component and four other variables were 0.95, 0.90, .0.86 and 0.85 respectively. Conclusion: using effective psychological empowerment components can play a major role in stuff's productivity.